2017
DOI: 10.1016/j.toxrep.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Safety assesment of Bacillus clausii UBBC07, a spore forming probiotic

Abstract: Probiotics are vital bacteria that colonize the intestine and modify its microflora with benefits for the host. Very few members of the Bacillus group are recognized as safe for use and hence only a few strains are available as commercial preparations for application in humans and animals. Acute and subacute studies in rats were conducted to establish safety of Bacillus clausii (B. clausii) UBBC07. In the acute toxicity study, the oral LD50 for B. clausii UBBC07 was found to be >5000 mg/kg (630 billion cfu/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 28 publications
3
35
0
1
Order By: Relevance
“…These results suggest consumption of B. clausii is safe for humans. 27 In conclusion, resistant traits found in B. clausii spore suspension (Benegut®) in our study were similar to those reported from other commercial preparations of Bacillus strains. Benegut® can be a useful source of improving the intestinal imbalance of microbial flora; and effective treatment of diarrhea and other intestinal malfunctions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results suggest consumption of B. clausii is safe for humans. 27 In conclusion, resistant traits found in B. clausii spore suspension (Benegut®) in our study were similar to those reported from other commercial preparations of Bacillus strains. Benegut® can be a useful source of improving the intestinal imbalance of microbial flora; and effective treatment of diarrhea and other intestinal malfunctions.…”
Section: Discussionsupporting
confidence: 89%
“…25 Analysis of the whole genome sequence of B. clausii has revealed that the antibiotic resistance genes are present in chromosomal DNA which is intrinsic and not transferable. 27 Toxin genes were also found to be absent. These results suggest consumption of B. clausii is safe for humans.…”
Section: Discussionmentioning
confidence: 98%
“…B. cereus was among the primary microbes associated with baby food contamination as reported by FAO/WHO Expert Consultations [ 7 ]. In spite of that B. cereus was classified as category C or of low risk, its prevalence in infant food was sufficiently high to cause food borne infection outbreaks [ 8 , 9 ]. B. cereus spores are resistant to many processes as low and high temperatures, desiccation, disinfectant agents, ionization, radiation and ultraviolet light [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus clausii UBBC07 (MTCC 5472) is a Gram-positive, spore-forming, motile, rod-shaped, non-toxic, and safe probiotic bacterium (Lakshmi et al, 2017) available commercially in the form of spore-suspension and dry formulations in India. Clinically, the consumption of UBBC07 [2 × 10 9 colony-forming unit (CFU)] capsule (twice a day) for 10 days was found to be safe and effective to alleviate the symptoms of acute diarrhea in adults (Sudha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%